Functional dependence and associated factors of the elderly population in a health macro-region - Araújo, Ingrid Vitória de Sousa; Oliveira, Nayara Gomes Nunes; Marchiori, Gianna Fiori; Tavares, Darlene Mara dos Santos (Acta Fisiátrica, 2020)
Objective: To verify the functional dependence to perform basic, instrumental and advanced activities of daily living among the older people, and associated factors. Method: Cross-sectional an analytical study, developed with 1.611 older people from the community of a Health Macro-region of the State of Minas Gerais. In data collection, the following were applied: Mini-Mental State Examination; Structured questionnaire prepared by the Collective Health Research Group; Brazilian version of the Short Physical Performance Battery; Katz index; Lawton & Brody and Advanced Activities of Daily Living scales and the frailty phenotype. Results: 6.5% of the older people were dependent for basic activities; 70.7% partial/total dependent for instrumental activities and 25.1% had less participation in advanced activities. Dependence on basic and instrumental activities of daily living associated with the age group of 80 years or more (p= 0.001; p<0.001); presence of 5 or more morbidities (p= 0.023; p= 0.017); disability/poor physical performance (p<0.001; p<0.001) and pre-frailty/frailty (p= 0.015; p<0.001), respectively. Dependence on instrumental activities was also associated with no schooling (p<0.001). The lower participation in advanced activities was associated with no schooling (p<0.001); individual monthly income ≤ 1 minimum wage (p<0.001); disability/poor physical performance (p<0.001) and pre-frailty/frailty (p<0.001). Conclusion: The older adults showed a higher percentage of dependence to perform instrumental activities. Physical health is related to the functional dependence of the elderly, regardless of the complexity of daily activities; and should be considered when planning nursing interventions aimed at preventing and / or rehabilitating functional decline in this age group.